Acute Thrombotic Occlusion of the Popliteal Artery following Knee Dislocation: A Case Report of Management, Local Unit Practice, and a Review of the Literature - Anthony Dean Godfrey; Fadi Hindi; Callum Ettles; Mark Pemberton; Perbinder Grewal (Case Reports in Surgery)
Arterial complications following traumatic knee injury are relatively rare but mandate timely recognition and treatment to avoid significant comorbidity and medicolegal ramifications. In this report we describe a case of acute thrombotic occlusion of the popliteal artery occurring after knee dislocation, successfully repaired by intimal fixation and a limited venous patch reconstruction. We present a review of local practice in screening vascular injuries following knee dislocation, aligned with a review of the literature and considerations for practice.